Land market, urban rent, and housing problem: a theoretical approximation from the City of Buenos Aires (Huellas, 2020)
This article makes a theoretical approach to the functioning of the land and housing markets in modern cities, taking as a starting point the housing problem in the City of Buenos Aires. After analyzing the main determinations of these markets - land rent, real estate speculation, supply-demand mismatch, etc. -; it becomes clear that the increasing difficulty that vast groups of the urban population find in accessing adequate housing, that is, the housing deficit and the expansion of the informal housing market, is the result of structural conditions in which the market-oriented urban space production is framed in capitalist cities. In order to compensate for the dysfunctionalities of the market and respond to the housing needs of the insolvent sector, public policy intervention in terms of urban and housing planning is necessary, but it must be admitted that the structural causes will continue to subsist given the nature of the commercial institution as an agent of urban space production.
Keywords: urban rent; housing problem; housing; informality; real estate speculation